Efficacy and safety of Kanglaite injection combined with chemotherapy for women breast cancer: A protocol for systematic review and meta-analysis of randomized clinical trials. Issue 22 (4th June 2021) - Cheng, Shengli; Qu, Biao; Qiu, Xiaoxia; Li, Nannan; Wang, Xiaoli; Hao, Jiahu
Abstract: Background: Breast cancer was the second cause of cancer death and approximately accounted for 30% of all newly diagnosed cancer in American women. Adjuvant chemotherapy is the preferred treatment approach for breast patients. Kanglaite injection (KI) was commonly used as adjuvant chemotherapy combined with chemotherapy for women breast cancer which could increase chemotherapy efficacy and alleviate chemotherapy drugs induced adverse events, however, the efficacy and safety for KI combined western medicine remains controversial. Thus, we conducted this protocol of systematic review and meta-analysis to estimate the efficacy and safety of KI combined with western medicine for women breast cancer. Methods: This study will search electronic database included English medicals databases and Chinese databased up to May 2021. The main outcomes of this study include clinical efficacy rate. Adverse reaction rate, Karnofsky Performance Status and immune function were defined as the secondary outcomes. Results: This protocol study will comprehensively evaluate the efficacy and safety of KI combined with chemotherapy for women breast cancer. Conclusion: This protocol for systematic review and meta-analysis will evaluate the efficacy and safety of KI combined with chemotherapy for women breast cancer, aiming to provide optimal therapy for women breast cancer patients.